Assessment of Thyroid Hormones and Liver enzymes among Epileptic Adult Patients Treated with Carbamazepine Versus Levetiracetam (Tikrit Journal of Pharmaceutical Sciences, 2018)
Aim of the study was to evaluate and compare the effect of carbamazepine and levetiracetam on thyroid hormones and liver enzymes in adult epileptic patients.Method: This Cross-Sectional study involved 105 subjects of them seventy patients having Primary Idiopathic Epilepsy with Normal Neurological Examination and Normal Brain imaging treated with either Carbamazepine or Levetiracetam monotherapy for more than 3 months enrolled and divided into two groups: first group included thirty five patients, treated with Carbamazepine monotherapy and Second group included thirty five patients, treated with Levetiracetam monotherapy, while the remaining thirty five healthy individuals' age and sex matched with the patients were considered as a control group. Thyroid function tests and Liver Function Test were measured for epileptic patients and control subjects.Result: Astatistically significant low level of TT3and TT4 with normal TSH level was observed in epileptic patients, who treated with carbamazepine when compared with control group, while there was no statistically significant difference in the level of TT3, TT4 and TSH in epileptic patients who treated with levetiracetam as compared with control group. A statistically significant high level of AST and ALT with normal ALP level was observed in epileptic patients who treated with carbamazepine when compared with control group, while those treated with levetiracetam showed a significantly high level of ALP as compared with control group. Conclusion: carbamazepine had the ability to decrease thyroid hormone levels and increase hepatic enzyme level while levetiracetam had no effect on thyroid hormone levels with ability to increase ALP liver enzyme level.